Notes on the policies Bologna post: the case of the implementation of the system ETCS - Reboucas Porto Junior, Francisco Gilson; Moraes, Nelson Russo de [UNESP]; Barbosa e Silva, Rodrigo (Univ Caxias Sul, Centro Ciencias Comunicacao, 2015)
Bologna Process has attracted the attention of researchers from all over the world. It deals with a changing in educational processes never seen before. Under guiding issues, we approached political, social and educational aspects in Sorbonne Declaration (1998), Bologna Declaration (1999) and the consolidation of educational policies in conferences in Prague (2001), Berlin (2003), Bergen (2005), London (2007), Louvain (2009) and Bucharest (2012), focusing on European Credit Transfer System (ECTS). We find out that, besides the meaningful advances in policies implementation regarding Bologna, difficulties in instructional alignment, common to educational changes reaching this dimension.
Keywords: Journalism; Communication; Education; Teaching; Bologna Process